Stability of alkyd emulsion resins and anti-corrosion properties of water-based alkyd emulsion paints - Le Huy Cuong Huynh; Khanh Xuan Phan; Thanh An Truong; Hung Thuy Nguyen (Vietnam Journal of Science, Technology and Engineering)
Vegetable oils extracted from nuts are a useful source of raw materials for the paint industry. Alkyd resins were synthesised with a content of 50 wt% soybean oil. The synthesised alkyd resins were evaluated by Fourier trans- form infrared spectroscopy (FTIR) and gel permeation chromatography (GPC). Particle size was determined using dynamic light scattering (DLS). Soybean oil alkyd resins were emulsified with the anionic surfactants linear alkyl- benzene sulfonate (LAS)/sodium lauryl sulphate (SLS) and the nonionic surfactant nonyl phenol ethoxylate (NP9) in an aqueous solvent. The anti-corrosion properties of the alkyd emulsion coatings were determined using the electrochemical method. The results showed that with a content of 13 wt% of the mixture of LAS and NP9 surfac- tants, the formed alkyd emulsion resins had good stability. Alkyd emulsion paint with a water solvent achieved the physicochemical properties required for steel protection. However, the anti-corrosion properties of the fabricated alkyd emulsion coatings need to be improved. The use of water as a solvent is gradually replacing organic solvents, with many prospects for new applications.